2016
DOI: 10.1007/s12687-016-0275-3
|View full text |Cite
|
Sign up to set email alerts
|

Engaging diverse populations in biospecimen donation: results from the Hoy y Mañana study

Abstract: The disproportionately lower number of certain subpopulations participating in clinical and prevention research has a significant impact on the representativeness of scientific outcomes. The Hoy y Mañana program (Today and Tomorrow) was developed as a culturally and linguistically appropriate education program to engage diverse medically underserved populations without a cancer diagnosis in biospecimen donation for cancer genomic research. Participants were recruited to in-depth community-based educational pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…This finding differs from recent studies demonstrating that African Americans are willing to donate biospecimens when offered the opportunity. Rodriguez et al found that community engagement efforts and initiatives that provide biospecimen donation education that also is tied to on‐site opportunities to donate biospecimens address awareness and access among diverse racial and ethnic minority participants, leading to actual participation . Study context and site characteristics are potentially significant factors in explaining these differences and may be overshadowed in the pooled analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding differs from recent studies demonstrating that African Americans are willing to donate biospecimens when offered the opportunity. Rodriguez et al found that community engagement efforts and initiatives that provide biospecimen donation education that also is tied to on‐site opportunities to donate biospecimens address awareness and access among diverse racial and ethnic minority participants, leading to actual participation . Study context and site characteristics are potentially significant factors in explaining these differences and may be overshadowed in the pooled analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Rodriguez et al found that community engagement efforts and initiatives that provide biospecimen donation education that also is tied to on-site opportunities to donate biospecimens address awareness and access among diverse racial and ethnic minority participants, leading to actual participation. 16 Study context and site characteristics are Cancer March 1, 2020 potentially significant factors in explaining these differences and may be overshadowed in the pooled analysis. In addition, transparency with regard to the actual research opportunity and request for biospecimens is critical to engaging underserved communities with a specific study or actual intervention versus constructs as presented in the survey.…”
Section: Race and Ethnicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the studies conducted by Gao et al in 2014 and Rodriguez et al in 2016, we discovered that individuals would be willing to donate blood biospecimens for research if they were given an opportunity to donate immediately after a biospecimen educational session . However, although both of those studies focused on engaging the general community and required participants to attend an in‐depth (45‐60 minutes) biospecimen educational seminar before donating, our approach included engaging both patients with cancer and the general community and did not require participants to attend an in‐depth educational session on biospecimens.…”
Section: Discussionmentioning
confidence: 58%
“…Establishment of prospective multi‐ethnic cohorts with adequate patient outreach is critical to understanding the diversity of outcomes in such populations (Anderson et al , ). In addition, the establishment of multi‐ethnic cohort studies with sufficient availability of biospecimens for genetic and other molecular studies is needed to identify candidate biomarkers or therapeutic targets, the applicability of which may differ among racial and ethnic groups (Rodriguez et al , ). Therefore, biomarker studies should be adequately powered to identify high‐risk signatures in these groups.…”
mentioning
confidence: 99%